The aftermath of the Cameron Highlands Floriculturist Association case on trade related associations and price fixing agreements in Malaysia / Agayar Kanni Ramaiah - Ramaiah, Agayar Kanni (2014)
Trade related associations are an important feature of a trade or industry in the business world and undeniably play a significant role in not just promoting and protecting their business rights with respect to government trade policies and related trade or industry rights but also involved in activities which potentially anti -competitive in nature. Although this trade associations is per se nonprofit making and purely done to benefit the players in the industry but universally known in the guise of "standard setting‟ enter agreements or understanding which compromises the consumers welfare and market liberalization of that trade or industry. The Cameron Highlands Floriculturist Association (CHFA) case came at the height of Malaysian government‟s attempt and effort to introduce, regulate and control the anti-competition regulations under the Competition Act 2010 (CA 2010) in Malaysia. This case was not just the very first landmark case to be heard and recorded by the Malaysian Competition Commission (MyCC) but in fact the very first case itself was on an anti competition conduct related to a trade associations and price fixing conduct in Malaysia. The case did not just came as a surprise to the related trade associations but as a wakeup call to all trade related associations to be aware of the CA 2010 which came into force in January 2010.This paper analyzes the impact of the CA 2010 in the light of the decisions made in the CHFA with respect to anti competition practice such as price fixing and other prohibited activities or agreements among the players of the trade related associations in Malaysia.